Teachers’ attitudes to cultural diversity: Results from a qualitative study in Russia and Taiwan - Wang, Jui-Sheng; Lan, Jesse Yu-Chen; Khairutdinova, Rezeda R.; Gromova, Chulpan R. (Frontiers in Psychology, 2022)
This study examined elementary school teachers’ attitudes toward immigrant students and their families in Russia and Taiwan. Qualitative methodology was used for data collection. Teachers’ attitudes and conceptual orientations toward cultural diversity in the classroom were identified. Teachers’ attitudes were categorized into three groups: Attitudes toward children, parents, and diverse ethnic groups. The study found that country-specific attitudes were similar. Both countries prioritize cognition. The Russian teacher may not acknowledge cultural variance (personal attitude) and hold all students to the same standards (professional attitude). Prior experiences have made the Taiwanese instructor more accepting of cultural variety. Teachers of immigrant children often tackle language concerns. Some instructors are less welcoming of immigrants at home. Educators judge immigrants depending on their natal country. These impressions may encourage prejudice, some say. Many teachers dislike minority students. Negative attitudes concerning student achievement lead to low expectations. Instructors use more tolerant approaches with more multicultural engagement.